Evaluating The Efficacy of Repetitive Transcranial Magnetic Stimulation In Treating Neurodegenerative Cerebellar Ataxia: A Systematic Review and Meta-Analysis - Angelina Wandana; Jeanne Alexandra; Agung Junnata; Daniel Natanael; Raisa Kireyna Nurfajrina; Michelle Valencia Bunjamin (Lumina : Indonesian Journal of Neurology, 2025)
Introduction: Neurodegenerative diseases such as multiple system atrophy (MSA), spinocerebellar ataxia (SCA), and Friedreich’s ataxia (FRDA) progressively impair the nervous system, affecting approximately 15% of the global population. Repetitive transcranial magnetic stimulation (rTMS), a non-invasive method, may promote neuroplasticity. The cerebellum, central to motor control and neural connectivity, is a promising rTMS target. Therefore, this research aims to evaluate the efficacy of rTMS in treating neurodegenerative cerebellar ataxia. Methods: A systematic review and meta-analysis was conducted per PRISMA guidelines, searching ten databases (to August 9, 2025). Eligible studies were RCTs comparing rTMS with sham in cerebellar ataxia. The review was registered on PROSPERO (CRD420251127471). Study quality was assessed with Cochrane RoB 2.0; meta-analysis used Review Manager 5.4.1, and meta-regression was performed in JASP 0.19.3. Results: Seven RCTs involving a total of 256 patients were included. rTMS significantly improved SARA (SMD = -0.84, p = 0.004, I² = 73%). ICARS showed no significant difference (SMD = -0.82, p = 0.43, I² = 96%). Meta-regression and sensitivity analysis were done to find key heterogeneity sources. Most studies had low bias. Conclusions: rTMS significantly improves SARA scores in neurodegenerative cerebellar ataxia if compared to sham, while ICARS shows insignificant differences. Further research is needed.Keywords: Neurodegenerative ataxia, Repetitive Transcranial Magnetic Stimulation, Sham-controlled